STATIC RESERVOIR MODELLING AND HYDROCARBON VOLUME ESTIMATION IN BATURAJA FORMATION, BETA AREA, SOUTH SUMATRA BASIN - Anggraini Sarumaha, Elvira
Beta Area is an area that has the potential to produce gas on the Baturaja Formation, South Sumatra Basin based on the result of tested data on exploration wells. Administratively, Beta Area is located in Ogan Komering Ulu Regency, South Sumatra Province. This area physiographically lies in the Tertiary-aged of Sumatra back-arc basin. Geological studies and reservoir modeling are focused at FS0-FS4 sequence interval on Baturaja Formation comprise of limestone. This study aims to comprehend the geological condition, determining reservoir static model, and estimating hydrocarbon volume in the Beta Area. Data used in this study consist of wireline logs, cutting description, biostratigraphy report, and three-dimensional seismic data. Several methods used in this study comprise of well correlation using sequence stratigraphy concept, petrophysical analysis, analysis of facies and depositional environment, isopach determination, creating depth structure, three -dimensional structural model, facies and petrophysical properties models, determination of fluids contact, and hydrocarbon volume estimation. The outcomes from all those methods show an overview of the geological condition and the estimation of its hydrocarbon volume in the Beta Area. The results of the well analysis show that the study area deposited in the transgressive phase comprises of wackestone limestone and shale composing facies association as well as the depositional environment which is restricted platform, open marine, platform sand shoals, and platform margin reef. The prospect areas are divided into three areas and bounded by fault boundary. The volume estimation (IGIP) result shows that the volume of gas in place from Prospect Area A is 6 BSCF, Prospect Area B is 50 BSCF, and Prospect Area C is 86 BSCF